Antimicrobial susceptibility profile of enterotoxigenic and enteropathogenic Escherichia coli isolates obtained from fecal specimens of children with acute diarrhea - Patrícia Luciana de Oliveira; Caroline S. Paula; Lisandra D. Rocha; Guilherme B. Collares; Roger T. Franco; Carolina P. Silva; Luiz M. Farias; Francisco José Penna; Edilberto N. Mendes; Teresa Cristina A. Ferrari; Paula P. Magalhães (Sociedade Brasileira de Patologia Clínica, 2017)
ABSTRACT Among the diseases which etiopathogenesis is associated with Escherichia coli, acute diarrhea stands out. Studies on the characterization of the antimicrobial susceptibility profile contribute to the selection of appropriate empirical antimicrobial therapy. In this study, the antimicrobial susceptibility profile of 98 enterotoxigenic E. coli (ETEC) and enteropathogenic E. coli (EPEC) strains isolated from fecal specimens of children with acute diarrhea was evaluated. The resistance rates to ampicillin, sulfamethoxazole/trimethoprim, amoxicillin/clavulanate, and nalidixic acid were high, ranging from 34.7% to 10.2%. The result of this research recommends the use of cefotaxime and ceftriaxone for the empirical treatment of children with acute diarrhea which the etiology suggested is ETEC or EPEC.